PENGARUH PEMBERIAN SUBKRONIK EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus Sabdariffa L.) TERHADAP KADAR SGPT SGOT DAN ALP - Nurkhasanah Nurkhasanah; Moch. Saiful Bachri; Nofa Risma Azis (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2016)
Roselle (Hibiscus sabdariffa L.) has been known as traditional medicinal plants. It needed to evaluate the safety of roselle extract on long-term oral administration. The research aimed to determine the savety of ethanolic extract of roselle calyx. Subchronic toxicity study of ethanolic extract of roselle calyx had been carried out on 60 Sprague Dawleys (SD) rats for 28 days. The roselle extract was administered orally every day, with doses of 50,100 and 200 mg/kgBW. There are 2 satellite groups, kept for another 14 days after the treatment in order to detect a delayed occurrence of toxic effect. Satellite group was given extract 200 mg/kgBW for 28 days and followed aquadest treatment for 14 days. At the end of experiment the blood was collected for meansuring SGPT, SGOT and ALP activity. The result showed that treatment of roselle calyx extract had no significant changes in SGPT SGOT, ALP activity. The delayed effect was not also observed. The ethanolic extract of roselle calyx didnt show toxic effects on the liver on subchronic administration.